Epidemiological transition in Peru: analysis of mortality records from 2003 to 2016 - Bernabe-Ortiz, Antonio (2020)
Objective: to describe the existing patterns of mortality in Peru, at the national and regional level. Materials and methods: a secondary analysis using national death records from 2003 to 2016 was conducted. The Global Burden of Disease 20017 approach was utilized to group underlying causes of death into five groups: non-communicable diseases, infectious diseases, maternal and neonatal, nutritional, and injury deaths. The Mann-Kendall tau test was used to assess trends and changes of causes of death over time. Results: between 2003 and 2016, a total of 1′295,290 deaths at the national level were recorded, but only 698,037 records were analyzed. For 2003, 63.9% of deaths were attributed to non-communicable diseases, whereas 16.9% were due to infectious diseases, and 8.8% for injuries. For 2016, 83.6% of deaths were attributed to non-communicable diseases (p-value for trends < 0.001), whilst 8.6% of deaths were due to infectious diseases (p-value for trends < 0.001), and 5.4% were due to injuries (p-value for trends < 0.001). Similar results were obtained when analyses were conducted by sex and by regions. Conclusions: from 2003 to 2016, the proportion of deaths attributable to non-communicable disease have increased in Peru. These findings were similar for both, males and females, and for the 25 regions in the country, where the non-communicable diseases are the first cause of death.